2006
DOI: 10.1007/s00213-006-0540-y
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter occupancy induced by paroxetine in patients with major depression disorder: a 123I-ADAM SPECT study

Abstract: Using (123)I-ADAM SPECT, treatment with paroxetine 20 mg/day leads to more than 60% SERTocc on average in cerebral regions with known high SERT density. Data from this study do not support the existence of SERT availability differences between drug-free MDD patients and healthy volunteers. Finally, the E (max) model is suitable for the study of paroxetine Cp relationship to (123)I-ADAM SPECT-measured SERTocc. This approach may be useful for pharmacokinetic-pharmacodynamic relationships in drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 30 publications
(30 reference statements)
3
41
1
Order By: Relevance
“…Our results confirm previous reports of similar SERT availability in the midbrain and diencephalon in MDD patients and healthy subjects [14][15][16][17][18]. Other studies have shown increased [19] or decreased [7][8][9][10][11][12][13] SERT availability in MDD patients compared with healthy subjects.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…Our results confirm previous reports of similar SERT availability in the midbrain and diencephalon in MDD patients and healthy subjects [14][15][16][17][18]. Other studies have shown increased [19] or decreased [7][8][9][10][11][12][13] SERT availability in MDD patients compared with healthy subjects.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
“…Studies comparing depressed patients with healthy subjects have shown decreased [7][8][9][10][11][12][13], unchanged [14][15][16][17][18] or increased [19] SERT availability in MDD patients. A negative correlation between SERT availability and the severity of depression, measured in terms of Hamilton depression rating scale (HDRS) scores, has been reported in patients with primary MDD [9] or Wilson's disease [20].…”
mentioning
confidence: 99%
“…On the contrary, paroxetine inhibition of [ 11 C]McN5652 was consistent with an I max of 100 % (Kent et al 2002). Importantly, the obtained K i values were comparable, 2.7 ng/mL for [ 1 2 3 I]ADAM and 2.9 ng/mL for [ 11 C]McN5652, respectively, and the authors argued that the difference in I max was likely due to technical factors (Catafau et al 2006). We considered using higher doses of SSRIs to further evaluate I max but found that 5.0 mg/kg of escitalopram significantly decreased blood pressure and heart rate and did not continue considering animal welfare reasons.…”
Section: Discussionmentioning
confidence: 66%
“…For this reason final occupancy values were determined based on the obtained K i and ID 50 values. (Catafau et al 2006). On the contrary, paroxetine inhibition of [ 11 C]McN5652 was consistent with an I max of 100 % (Kent et al 2002).…”
Section: Discussionmentioning
confidence: 93%
“…In one such study, the occupancy at [ 123 I]β-CIT sites by sertraline was nearly 50% and correlated with treatment response after six weeks in OCD patients (Zitterl et al, 2009), whereas occupancy by paroxetine was in the range of 50-79% in most MDD patients and also correlated with treatment response, but only in the subgroup with a particular allele of the SERT promoter (Ruhe et al, 2009b). [ 123 I]-ADAM SPECT in MDD patients treated with paroxetine revealed a maximal occupancy of 70% of SERT, when calculated by an E max model (Catafau et al, 2006). Thus, our findings suggest a somewhat lower occupancy compared to earlier studies.…”
Section: Discussionmentioning
confidence: 95%